Metastatic Periampullary Tumor from Hepatocellular Carcinoma Presenting as Gastrointestinal Bleeding - Amir Kashani; Nicholas N. Nissen; Maha Guindi; Laith H. Jamil (Case Reports in Gastrointestinal Medicine)
Periampullary tumors constitute a number of diverse neoplastic lesions located within 2 cm of the major duodenal papilla; among these, metastatic lesions account for only a small proportion of the periampullary tumors. To our knowledge, a metastatic periampullary tumor from hepatocellular carcinoma has never been reported. A 62-year-old male reported to our institute for fatigue and low hemoglobin. His medical history was remarkable for multifocal hepatocellular carcinoma (HCC) treated with selective transcatheter arterial chemoembolization (TACE). An esophagogastroduodenoscopy (EGD) was performed which revealed a periampullary mass. Histopathology was consistent with metastatic moderately differentiated HCC. Two endoloops were deployed around the base of the mass one month apart. The mass eventually sloughed off and patient’s hemoglobin level stabilized. We postulated that periampullary metastasis in this patient was the result of tumor fragments migration through the biliary tracts and that TACE which increases tumor fragments burden might have played a contributory role. Metastasis of HCC to the gastrointestinal (GI) tract should be considered as a cause of GI bleeding.